Examining the remaining Rock Art at Linton, Eastern Cape, and its relationship with the Linton Panel at the Iziko South African Museum in Cape Town - Oster, Sandee Michelle (University of the Witwatersrand, Johannesburg, 2023)
The Linton panel has been the subject of great awe for many decades. It has been displayed in various exhibits worldwide and the subject of multiple research publications. However, its history and origin are not nearly as well understood as once believed, as a large part of its past has been omitted or forgotten. In this dissertation the images of not only the Linton panel are discussed, but those that remain in the shelter from whence it came are brought out of obscurity. How the panel came to be where it is today and the images’ relationship with the shelter and the remaining paintings are examined. Lastly, a forgotten piece of the shelter, a second panel, will be examined in greater detail than ever before: how it fell into relative obscurity and what its images tell us about the Linton shelter and its artists’ beliefs and purposes.
A Dissertation submitted in fulfilment of the requirements for the e Degree of Master of Science, to the Faculty of Science, School of Geography, Archaeology and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Linton; Rock Art; Object Biography; Sister Panel; Linton Panel; UCTD; SDG-11: Sustainable cities and communities